Discrete-time predictive control with overparameterized delay-plant models and an identified cancellation order - Kowalczuk, Zdzisław; Suchomski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents several solutions to the discrete-time generalized predictive (GPC) controller problem, including an anticipative filtration mechanism, which are suitable for plants with nonzero transportation delays. Necessary modifications of the GPC design procedure required for controlling plants based on their non-minimal models are discussed in detail.
Keywords: delay plants; overparameterization; system design; predictive control; robust control synthesis; adaptive control